DIREITO INDÍGENA EM ESCOLAS GUAJAJARA: Apontamentos para a formação de professoras(es) no Maranhão - CARVALHO, Francisco José Ferreira (2024)
The research analyzes the insertion of the Discipline of Indigenous Law in the Gianni Sartori Indigenous School Teaching Center, located in the Juçaral community, southwest region of the State of Maranhão, belonging to the Araribóia indigenous land, in the municipality of Amarante do Maranhão, with a view to building a Guidance Guide didactic-pedagogical for the training of teachers at that institution. In addition to this, other objectives are added: a) to identify what theoretical conceptions about Indigenous Law the teachers at the Gianni Sartori Indigenous School Teaching Center have; b) verify how the history of Indigenous Education and Indigenous Law are articulated at the Gianni Sartori Indigenous School Teaching Center; c) find out how Indigenous Law is worked on at the Gianni Sartori Indigenous School Teaching Center and whether there is a reference to this conceptual category in its Pedagogical Political Project: d) find out if there is ongoing training aimed at Indigenous Law in conjunction with the Guidelines National Curriculums for Indigenous School Education and with the Curricular References for Indigenous Education of the State of Maranhão at the Gianni Sartori Indigenous School TeachingCenter and prepare an Ebook with theoretical-methodological aspects on the teaching of Indigenous Law, with a view to contributions to training of students and teachers at the Gianni Sartori Indigenous School Teaching Center. The research, therefore, investigates Indigenous School Education in the State of Maranhão, based on the 1988 Constitution, the Law of Guidelines and Bases of National Education (LDB 9,394/96), the National Education Plan (Law nº 10,172) and in Resolution No. 5 of 2012, which seek to guarantee native peoples a specific and differentiated education; bilingual and intercultural, valuing the traditions and ancestry of indigenous peoples. The study is therefore organized into six sections. The first section describesthe introduction, justification and objectives of the research, characterization, delimitation of the problem and the interest in the research. The second section discusses the curricular componentof Indigenous Law and Decoloniality, presenting elements about the decolonial curriculum and Indigenous School Education; the third discusses the Training of teachers in Indigenous School Education. The fourth section presents the research method and methodological procedures, aswell as the paths outlined to achieve the objectives, in addition to describing the Pedagogical Guidelines Guide, which is a product of this investigative work, aiming to be a supporting teachingmaterial to the indigenous teacher who teaches this subject. The fifth section addresses the Indigenous Law curricular component at the Gianni Sartori Indigenous School and the sixth section presents the conclusive considerations of this study. This research, therefore, is based on Brazilian Legislation that deals with the indigenous educational issue and on the studies of Acosta (2016), Altini (2022), André (2016), Baniwa (2022), Bardin (1997), Diniz (1994 ), Dortier (2010), Freire (2020), Gonçalvez (2013), Grupioni (2022), Imbernón (2011), Landa (2017), Melià (2023), Nova (2013), Passos (2015), Sá (2014 ), Silva (2005), among others. It is, therefore, a qualitative research, which used the exploratory research approach, with the semi-structured interview and photographic records being used as data composition instruments and content analysis was the technique that based the structuring and the analysis of the collected data. Through this investigation, we concluded, therefore, the need for policies and programs for Indigenous School Education in Maranhão, focusing on the training of teachers. There are limitations, in the school investigated, regarding the understanding of the Indigenous Law Curricular Component by teachers and students. An aspect that points to continued training as a strategy to support the work of teachers in the area of Indigenous Law. It is in this sense that the preparation of the Pedagogical Guidelines Guide appears as a possibility to add to the teaching materials to be used by the teachers at the Gianni Sartori Indigenous School, assisting in their pedagogical practices.